1999
DOI: 10.1136/sti.75.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism in patients with HIV disease

Abstract: in order to identify those with a diagnosis of PE. Results: During the study period there were 3792 admissions of whom 10 (0.26%) had PE. All patients with PE presented with fever, seven were dyspnoeic, and seven had cough: all were thought initially to have respiratory infection. Only five patients had pleural pain. All 10 patients had abnormal baseline chest radiographs. The diagnosis in six was made by computed tomograph (CT) pulmonary angiography, in two was made by ventilation perfusion (V/Q) scanning, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…9 Although a relationship between HIV infection and VTE has been suggested in previously published case reports, 1-3 prior clinical studies have failed to confirm an association. 6,7 Autopsy studies on the other hand 4,5 have found a higher incidence of VTE in HIV1 patients than in the general population. 10 Our data also fail to show a significant correlation between HIV infection and VTE when uncorrected for age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 Although a relationship between HIV infection and VTE has been suggested in previously published case reports, 1-3 prior clinical studies have failed to confirm an association. 6,7 Autopsy studies on the other hand 4,5 have found a higher incidence of VTE in HIV1 patients than in the general population. 10 Our data also fail to show a significant correlation between HIV infection and VTE when uncorrected for age.…”
Section: Discussionmentioning
confidence: 96%
“…4,5 In contrast, clinical studies have not found a high incidence of VTE in HIV-positive (HIV1) individuals. 6,7 The latter reports did not examine the effect of age on the relationship between HIV status and VTE. Preliminary data at our hospital suggested a relatively high prevalence of HIV infection among patients under 50 years of age with VTE.…”
Section: Introductionmentioning
confidence: 96%
“…Studies mainly from the pre-HAART era estimated that the overall risk of VTE in patients with HIV infection was roughly 2-10-fold higher than expected in the general population [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, many studies were limited by small sample size [15,16,22,23] and a lack of a population-based comparison cohort [11][12][13]15,16,19,[21][22][23].AIDS-related opportunistic infections, neoplasms and HIV infection per se have been hypothesized to predispose patients to a hypercoagulable state [16]. Various other abnormalities in the haemostatic pathways of HIV-infected patients have also been reported [25][26][27].…”
mentioning
confidence: 99%
“…Many HIV-positive patients present with symptoms due to respiratory infections that are difficult to distinguish from PE. The diagnosis of PE still should be considered in HIV-positive patients with presumed respiratory infections who do not respond to antimicrobial therapy [76].…”
Section: Comorbid Diseasesmentioning
confidence: 99%